Gestión de ventas del bazar María José de la Ciudad de Babahoyo. - Suarez Hinojosa, Hillary Viviana (2022)
The present case study was developed with the purpose of publicizing the sales management of the Bazar María José in the city of Babahoyo, where it was shown that the place has been established in the sales market for many years, it is very lacking in the updates that are presented with globalization, such as inventory management, updating marketing platforms such as social networks and updating the client portfolio, but despite all the inconveniences it has had over time It is one of the most solid and trusted businesses for the Babahoyense population.. To carry out this case study, direct observation and questionnaire techniques were carried out with frequent customers and an interview with the owner of the establishment with key questions that helped to understand the situation that the place is going through and thus be able to determine and provide alternatives for improvement in the sales management of Bazar María José.